INNOVATIVE SOLUTIONS FOR DUST CONTROL IN COTTON GINING ENTERPRISES - Otamirzayev, Abdulkhadi (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Annotation. The article describes the technological process of primary processing of cotton, which is accompanied by a significant release of dust from technological and transporting machines into production premises and the atmosphere. The norm of air dust content in the production premises of a cotton gin plant is no more than 10 mg/m3. To create normal sanitary and hygienic conditions, production premises and individual dust-emitting installations are dedusted. Before exhaust dust-laden air is released into the atmosphere, it is also cleaned of dust. At the beginning of the technological process, during transportation and cleaning of raw cotton from impurities, mineral dust is mainly released from it and pollutes the air; at the end of the technological process, especially during linting and compaction, dust of organic origin is released. Despite the installation of the necessary dust removal equipment, many problems and unresolved issues remain.